2007
DOI: 10.1007/bf02913330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flaxseed(Linum usitatissimum) chutney on gamma-glutamyl transpeptidase and micronuclei profile in azoxymethane treated rats

Abstract: Antioxidant property of flaxseed chutney was evident by decreasing lipid peroxidation (TBARS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, a review of literature revealed that none of the herbal medications that patient 1 had taken (Lineum usitatissimum, Fumariaceae, Curcumin, and Silybum marianum) are known to cause a liver damage; in fact, several recent studies have shown a protective effect of these medications in states of liver injury. [21][22][23][24] Nevertheless, no study examined the combination of these herbal medications, thus, potential liver toxicity cannot be excluded. As to the second patient who was treated with fluconazole, although LFT abnormalities are associated with all of the azoles, these abnormalities are more likely with itraconazole and ketoconazole than with fluconazole 25,26 and the later seems to have a lower risk of treatment discontinuation because of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…However, a review of literature revealed that none of the herbal medications that patient 1 had taken (Lineum usitatissimum, Fumariaceae, Curcumin, and Silybum marianum) are known to cause a liver damage; in fact, several recent studies have shown a protective effect of these medications in states of liver injury. [21][22][23][24] Nevertheless, no study examined the combination of these herbal medications, thus, potential liver toxicity cannot be excluded. As to the second patient who was treated with fluconazole, although LFT abnormalities are associated with all of the azoles, these abnormalities are more likely with itraconazole and ketoconazole than with fluconazole 25,26 and the later seems to have a lower risk of treatment discontinuation because of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…People have been consuming flaxseeds since ancient times. In India, flaxseeds are still being consumed as food and also for medicinal purposes [19]. It has an important position among oilseeds because of its versatility.…”
Section: Flaxmentioning
confidence: 99%